Fibrocartilage Stem Cells in the Temporomandibular Joint: Insights From Animal and Human Studies - Fan, Yi; Cui, Chen; Li, Peiran; Bi, Ruiye; Lyu, Ping; Li, Yanxi; Zhu, Songsong (Frontiers in Cell and Developmental Biology, 2021)
Temporomandibular disorders (TMD) are diseases involving the temporomandibular joint (TMJ), masticatory muscles and osseous components. TMD has a high prevalence, with an estimated 4.8% of the U.S. population experiencing signs and symptoms, and represents a financial burden to both individuals and society. During TMD progression, the most frequently affected site is the condylar cartilage. Comprising both fibrous and cartilaginous tissue, condylar cartilage has restricted cell numbers but lacks a vascular supply and has limited regenerative properties. In 2016, a novel stem cell niche containing a reservoir of fibrocartilage stem cells (FCSCs) was discovered in the condylar cartilage of rats. Subsequently, FCSCs were identified in mouse, rabbit and human condylar cartilage. Unlike mesenchymal stem cells or other tissue-specific stem/progenitor cells, FCSCs play a unique role in the development and regeneration of fibrocartilage. More importantly, engraftment treatment of FCSCs has been successfully applied in animal models of TMD. In this context, FCSCs play a major role in the regeneration of newly formed cartilage. Furthermore, FCSCs participate in the regeneration of intramembranous bone by interacting with endothelial cells in bone defects. This evidence highlights the potential of FCSCs as an ideal stem cell source for the regeneration of oral maxillofacial tissue. This review is intended to detail the current knowledge of the characteristics and function of FCSCs in the TMJ, as well as the potential therapeutic applications of FCSCs. A deep understanding of the properties of FCSCs can thus inform the development of promising, biologically based strategies for TMD in the future.